2005
DOI: 10.1258/0022215053222824
|View full text |Cite
|
Sign up to set email alerts
|

Canalicular adenoma of the parotid gland

Abstract: Canalicular adenomas are a rare form of benign tumour that occur in salivary glands, occurring mainly in the upper lip and minor salivary glands of the buccal mucosa. The authors report the fifth case and the first in the otorhinolaryngological literature of a canalicular adenoma of the parotid gland. Its specific histological features are difficult to detect on fine needle aspiration and its multifocal nature can lead to recurrence and this must be considered in the clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
(22 reference statements)
2
15
0
2
Order By: Relevance
“…In general, is seems that CanAd may not develop in major salivary glands. Cases reported thus far in the major salivary glands (parotid, submandibular) are either not well illustrated or lack immunohistochemistry studies to confirm the diagnosis [25,64,69,[92][93][94][95]. Additional investigation is encouraged.…”
Section: Clinical Informationmentioning
confidence: 99%
“…In general, is seems that CanAd may not develop in major salivary glands. Cases reported thus far in the major salivary glands (parotid, submandibular) are either not well illustrated or lack immunohistochemistry studies to confirm the diagnosis [25,64,69,[92][93][94][95]. Additional investigation is encouraged.…”
Section: Clinical Informationmentioning
confidence: 99%
“…Se localiza en la cavidad oral con predilección por el labio superior (70 % a 90 % de los casos) y rara vez en otros sitios, como el paladar y la parótida (1,3,(5)(6)(7)(8)(9). Suele presentarse en adultos mayores de 50 años con máxima incidencia en la séptima década.…”
Section: Discussionunclassified
“…En la histopatología, se observan cordones de doble fila de células columnares o cúbicas con patrón alternante descrito como "collar de perlas" (beading): los cordones se disponen paralelamente en contacto estrecho y posteriormente se separan formando estructuras similares a ductos que dan origen al término "canalicular" de este tumor (1,3,4,(5)(6)(7)(8)(9)(11)(12)(13)(14). Estas estructuras similares a ductos, pueden dilatarse y llegar a conformar quistes con formaciones papilares (1,5,11).…”
Section: Hallazgos Morfológicosunclassified
“…Even less is known about its multicentric tendency and its characteristic localization to the upper lip. Some authors have suggested that the multifocal nature of this tumor is related to "field cancerization" caused by an unknown, [7,8] whereas others have suggested the multifocal dysplasia of developmental origin. [9] There is increasing evidence that canalicular adenoma is derived from ductal luminal cells.…”
Section: Discussionmentioning
confidence: 99%